Biolistrik dari Microbial Fuel Cell (MFC) Dual Chamber menggunakan Aspergillus Niger dengan Substrat Ampas Tebu - Sari Sekar Ningrum; Aidha Zulaika; Wike Handini; Djodi Dwi Prasetyo (Jurnal Penelitian Pendidikan IPA, 2023)
Electricity consumption is increasing, causing fossil fuels to run out more quickly. Various efforts are needed to develop renewable energy, including generating electricity. One of the developments in renewable energy comes from biomass. There are various types of biomass developed, one of which is biomass of microorganisms which carry out metabolic activities by utilizing organic material to produce metabolites which include energy. Microbial fuel cell (MFC) is a technology that produces electrical energy with the help of microorganisms that degrade organic materials through catalytic reactions or bioelectrochemical mechanisms from microorganisms. In this research, bioelectricity produced from MFC was tested using Aspergillus Niger with sugarcane bagasse as a substrate. The voltage value obtained from observations carried out for 15 days obtained a voltage in the range of 1.3-4.2 mV